Learning complexity-boundet rule-based classifiers by combining association analysis and genetic algorithms - Yi, Y.; Hüllermeier, Eyke (in Proceedings EUSFLAT-2005 4th International Conference on the European Society for Fuzzy Logic and Technology, Barcelona, Spain)

Fuzzy sets in machine learning and data mining: Status and prospects - Hüllermeier, Eyke (Fuzzy Sets and Systems)

Experience-based decision making: A satisficing decision tree approach - Hüllermeier, Eyke (IEEE Transactions on Systems, Man and Cybernetics-Part A: Systems and Humans)

Clustering of gene expression data using a local shape-based similarity measure - Balasubramaniyan, R.; Hüllermeier, Eyke; Weskamp, N.; Kämper, J. (Bioinformatics)

HGB: Basiswissen einschließlich Wechsel- und Scheckrecht Fälle und Lösungen auf interaktiver CD - Krimphove, Dieter

A Low Power Design for Embedded DRAMs with Online Consistency Checking - Oehler, Philipp; Hellebrand, Sybille
Keywords: WORKSHOP

Dynamic Routing: A Prerequisite for Reliable NoCs - Ali, Muhammad; Welzl, Michael; Hellebrand, Sybille
Keywords: WORKSHOP

Power Consumption Versus Error Correcting Capabilities in Embedded DRAMs - A Case Study - Oehler, Philipp; Hellebrand, Sybille
Keywords: WORKSHOP

The use of instant messaging in working relationship development: A case study - Trier, Matthias; Cho, Hee-Kyung; Kim, Eunhee (Journal of Computer-Mediated Communication)

IT-gestützte Modellierung und Analyse elektronischer Expertengemeinschaften (Modeling and Evaluation of Electronic Expert Communities) - Trier, Matthias (i-com)

Process-Oriented Production of Learning Units for Sustainable E-Learning Offerings - Müller, Claudia; Trier, Matthias; Herzog, Michael A. (E-Learning)

A Tool for IT-supported Visualization and Analysis of Virtual Communication Networks in Knowledge Communities - Trier, Matthias (Wirtschaftsinformatik 2005)

A Procedural Model for the Production of Reusable and Standard-Compliant E-Learning Offerings - Müller, Claudia; Trier, Matthias (Wirtschaftsinformatik 2005)

IT-Supported Visualization of Knowledge Community Structures - Trier, Matthias (Proceedings of the 38th Annual Hawaii International Conference on System Sciences)

Netzwerkorientiertes Wissensmanagement und seine Unterstützung durch Softwarewerkzeuge - Krallmann, Hermann; Trier, Matthias (Strategisches Wertschöpfungsmanagement in dynamischer Umwelt: Festschrift für Erich Zahn)

Adaptive scheduling for heterogeneous traffic flows in cellular wireless OFDM-FDMA systems - Valentin, Stefan; Gross, James; Karl, Holger; Wolisz, Adam (10th IFIP International Conference on Personal Wireless Communications/PWC'05, Comar, France, 2005)

Periodic real-time scheduling for FPGA computers - Danne, Klaus; Platzner, Marco (Proceedings of the Third International Workshop on Intelligent Solutions in Embedded Systems (WISES))

Memory-demanding Periodic Real-time Applications on FPGA Computers - Danne, Klaus; Platzner, Marco (Work-in-Progress Proceedings of the 17th Euromicro Conference on Real-time Systems (ECRTS))

A heuristic approach to schedule periodic real-time tasks on reconfigurable hardware - Danne, Klaus; Platzner, Marco (Proceedings of the 15th International Conference on Field Programmable Logic and Applications (FPL))

Quasiparticle bands and optical spectra of highly ionic crystals: AlN and NaCl - Bechstedt, F.; Seino, K.; Hahn, P. H.; Schmidt, Wolf Gero (Physical Review B)

Attracted by Long-Range Electron Correlation: Adenine on Graphite - Ortmann, F.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review Letters)

Calculation of reflectance anisotropy for semiconductor surface exploration - Schmidt, Wolf Gero (physica status solidi (b))

Quasiparticle and excitonic effects in the optical spectra of diamond, SiC, Si, GaP, GaAs, InP, and AlN - Hahn, P. H.; Seino, K.; Schmidt, Wolf Gero; Furthmüller, J.; Bechstedt, F. (physica status solidi (b))

VUV-ellipsometry on GaN: Probing conduction band properties by core level excitations - Esser, N.; Rakel, M.; Cobet, C.; Schmidt, Wolf Gero; Braun, W.; Cardona, M. (physica status solidi (b))

Initial Stage of Si(001) Surface Oxidation from First-Principles Calculations - Fuchs, F.; Schmidt, Wolf Gero; Bechstedt, F. (The Journal of Physical Chemistry B)

Understanding the optical anisotropy of oxidized Si(001) surfaces - Fuchs, F.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Coulombic Amino Group-Metal Bonding: Adsorption of Adenine on Cu(110) - Preuss, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review Letters)

Conformation-selective adsorption of 2,3-butanediol on Si(001) - Seino, K.; Schmidt, Wolf Gero (Surface Science)

Second-harmonic polarizability including electron-hole attraction from band-structure theory - Leitsmann, R.; Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Optical response ofπ-conjugated molecular monolayer adsorbed on the semiconductor Si(001) surface: A first-principles study - Hermann, A.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Phenanthrenequinone Adsorbed on Si(001): Geometries, Electronic Properties, and Optical Response - Hermann, Andreas; Schmidt, Wolf Gero; Bechstedt, Friedhelm (The Journal of Physical Chemistry B)

Optical Absorption of Water: Coulomb Effects versus Hydrogen Bonding - Hahn, P. H.; Schmidt, Wolf Gero; Seino, K.; Preuss, M.; Bechstedt, F.; Bernholc, J. (Physical Review Letters)

A study of impact of inband signalling and realistic channel knowledge for an example dynamic OFDM-FDMA system - Gross, James; Valentin, Stefan; Karl, Holger; Wolisz, Adam (European Transactions on Telecommunications)

Molecular electronic excitations calculated from a solid-state approach: Methodology and numerics - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Von der Ontologie zur Begriffsanalytik. Kants Beitrag zu den aktuellen Diskussionen über Metaphysik und Ontologie - Ficara, Elena (Philosophie von Immanuel Kant und die Gegenwart)

Vorwort - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)
Rezensionen: History and Philosophy of Logic 27 (2006), 198–200 (Dirk Schlimm); Bulletin of Symbolic Logic 12 (2006), 137–139 (R. Vilkko); NTM 15 (2007), 67–68 (K. Radbruch); Philosophiques 35 (2008), 612–613 (Y. Gauthier).

Einleitung: Oskar Becker und die Philosophie der Mathematik - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)

Rationalismus zwischen Vision und Wirklichkeit. Descartes, Leibniz und die Grenzen des Machbaren - Peckhaus, Volker (ForschungsForum Paderborn)

Comparison of Performance and Realization Effort of a Very Sparse Matrix Converter to a Voltage DC Link PWM Inverter with Active Front End - Round, Simon; Schafmeister, Frank; Pereira, Eduardo; Serpa, Leonardo; Kolar, Johann (Proc. 5th IEEJ International Power Electronics Conference (IPEC))

Analytical Calculation of the Conduction and Switching Losses of the Conventional Matrix Converter and the (Very) Sparse Matrix Converter - Schafmeister, Frank; Rytz, Christoph; Kolar, Johann (Proc. 20th IEEE Applied Power Electronics Conference (APEC))

Enhanced Control Scheme for Three-Phase, Three-Level Rectifiers at Partial Load - Ide, Peter; Schafmeister, Frank; Fröhleke, Norbert; Grotstollen, Horst (IEEE Transactions on Industrial Electronics)

Design and implementation of a hybrid energy supply system for railway vehicles - Li, R.; Pottharst, A.; Fröhleke, N.; Böcker, Joachim; Witting, K.; Dellnitz, M.; Znamenshchykov, O.; Feldmann, R. (Twentieth Annual IEEE Applied Power Electronics Conference and Exposition, 2005. APEC 2005.)

Design of Long-Stator Linear Motor Drives for RailCab Test Track - Grotstollen, H. (Journal of Power Electronics (JPE))

Convoy Operation of Linear Motor Driven Railway Vehicles, Kobe - Awaji, Japan - Henke, C.; Vöcking, H.; Böcker, Joachim; Fröhleke, N.; Trächtler, A. (LDIA 2005, The Fifth International Symposium on Linear Drives for Industry Applications)

Simulation of Power Electronic Circuits - Grotstollen, H.; Böcker, Joachim; Fröhleke, N. (ICSC 2005, Peking, China)

ZVZCS Isolated Converter for Renewable Energy System with Extra Wide Voltage Range - Li, R.; Fröhleke, N.; Böcker, Joachim; Ide, P. (International PCIM Conference 2005, Nürnberg, Deutschland)

Distributed Control Structure of the NBP Test Track with Linear Motor Driven Vehicles - Pottharst, A.; Grotstollen, H. (International Embedded Systems Symposium, Manaus, Brasil)

Impliziert Widerspruchsfreiheit Existenz? Oskar Beckers Kritik am formalistischen Existenzbegriff - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)

Becker und Zermelo - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)

19th Century Logic: Between Philosophy and Mathematics (Wiederabdruck) - Peckhaus, Volker (Mathematics and the Historian’s Craft. The Kenneth O. May Lectures)